A quietist Jihadi: the ideology and influence of Abu Muhammad al-Maqdisi - Wagemakers, Joas (Cambridge University Press, 2012)
Since 9/11, the Jordanian Abu Muhammad al-Maqdisi (b. West Bank, 1959) has emerged as one of the most important radical Muslim thinkers alive today. While al-Maqdisi may not be a household name in the West, his influence amongst like-minded Muslims stretches across the world from Jordan - where he lives today - to Southeast Asia. His writings and teachings on Salafi Islam have inspired terrorists from Europe to the Middle East, including Abu Mus'ab al-Zarqawi, the former leader of al-Qa'ida in Iraq, and Ayman al-Zawahiri, Osama Bin Laden's successor as the head of al-Qa'ida Central. This groundbreaking book, which is the first comprehensive assessment of al-Maqdisi, his life, ideology, and influence, is based on his extensive writings and those of other jihadis, as well as on interviews that the author conducted with (former) jihadis, including al-Maqdisi himself. It is a serious and intense work of scholarship that uses this considerable archive to explain and interpret al-Maqdisi's particular brand of Salafism. More broadly, the book offers an alternative, insider perspective on the rise of radical Islam, with a particular focus on Salafi opposition movements in Saudi Arabia and Jordan.